Solving the Crime of Petty Persecution Through the Restorative Justice Mechanism in a Progressive Legal Perspective - Hadi, Samsul; Harun, Rina Rohayu; Jiwantara, Firzhal Arzhi (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
The objectives of this study are to examine and analyze the application of Restorative Justice in handling minor assault crimes at the Lombok Tengah District Police Station and to analyze the legal challenges faced in applying Restorative Justice to optimize its application in minor assault cases from a progressive legal perspective at the Lombok Tengah District Police Station. The research method used in this study is normative empirical law using a legal approach, conceptual approach, sociological approach, and case approach. The legal materials used in this study include primary legal materials, secondary legal materials, and tertiary legal materials. The results of the study on the application of restorative justice in cases of minor assault within the Lombok Tengah Police Department were conducted in accordance with the mechanisms or rules outlined in Police Chief Regulation year 2021. In addition, the police offered reconciliation efforts to the victims and suspects based on cases that met the criteria for restorative justice and involved several other parties, such as religious leaders, traditional leaders, and community leaders, without any pressure, coercion, or intimidation from the Central Lombok Police, who acted as facilitators of minor assault cases. Second, the challenges faced in the implementation of restorative justice at the Lombok Tengah Police Station in resolving criminal cases of assault within the community include determining the value of compensation or restitution. Second, there are differing opinions between the victim and the victim's family regarding the peace efforts, where the victim does not wish to reconcile, while the victim's family desires reconciliation, considering long-term implications.